The effects of eccentric phase tempo in squats on hypertrophy, strength, and contractile properties of the quadriceps femoris muscle - Kojic, Filip; Mandic, Danimir; Duric, Sasa (Frontiers in Physiology, 2025)
IntroductionThe aim of the present study was to investigate the effects of eccentric phase tempo in squats on hypertrophy, strength, and contractile properties of the quadriceps femoris (QF) muscle.MethodsEighteen participants (10 males and 8 females, age 24.0 ± 1.7 years) with no resistance training (RT) experience in the last 8 months were randomized into two groups, each following a 7 week squat resistance training (RT) protocol with either a fast eccentric (FE, 1 s eccentric/0 s isometric/1 s concentric/0 s isometric) or slow eccentric (SE, 4 s eccentric/0 s isometric/1 s concentric/0 s isometric) tempo. The training intensity (60%–70% RM), the number of sets (3–4), and the rest intervals (120 s) were consistent in both groups. The study measured changes in quadriceps cross-sectional area (CSA), one-repetition maximum (1RM) strength, and muscle contractile properties such as contraction time (Tc) and radial displacement (Dm), using tensiomyography (TMG). An ANCOVA model with baseline values as covariates was used to examine between-group differences.ResultsResults showed significant strength gains in both groups, with the SE group achieving greater 1RM increases (effect size [ES] = 1.60 vs 0.99, p < 0.05). CSA increased for all QF muscles; however, the SE group exhibited significantly higher hypertrophy in the vastus lateralis (ES = 1.74 vs. 1.37, p < 0.05). TMG analysis revealed decreased Dm in the rectus femoris for both groups (p < 0.05), while Tc significantly (ES = 1.33, p < 0.01) increased in the SE group.DiscussionThese findings suggest that slower eccentric tempo in RT may optimize vastus lateralis hypertrophy and enhance strength while promoting muscle fiber-type specificity, contributing to the understanding of eccentric training’s role in muscle adaptation.